Demographic and clinical correlates of accelerometer assessed physical activity and sedentary time in lung cancer survivors - D'Silva, A.; Bebb, G.; Boyle, Terry; Johnson, S.; Vallance, J. (SPRINGER, 2018)
Copyright © 2017 John Wiley & Sons, Ltd. Objective: To determine demographic and clinical correlates of accelerometer assessed physical activity and sedentary time among a population-based sample of lung cancer survivors. Methods: Lung cancer survivors in Southern Alberta, Canada (N = 527) were invited to complete a mailed survey assessing socio-demographics and wear an Actigraph® GT3X+ accelerometer for 7 days. Average daily minutes of physical activity and sedentary time were derived from the accelerometer data. Accelerometer data were processed using standard Freedson cutpoints, and correlates of physical activity and sedentary time were determined with linear regression. Results: A total of 127 lung cancer survivors participated (mean age = 71 years), for a 24% response rate. Moderate-to-vigorous physical activity was negatively associated with being > 60 years of age (ß = -7.4, CI: -14.7, -0.10). Moderate-to-vigorous physical activity accumulated in 10-minute bouts was associated with receiving surgery and adjuvant chemotherapy (ß = 9.1, CI: 2.1, 16.1). Sedentary time was associated with being > 60 years of age (ß = 32.4, CI: 3.1, 61.7), smoking (ß = 63.9, CI: 22.5, 105.4), and being overweight/obese (ß = 28.6, CI: 6.4, 50.1). Conclusion: Age, smoking history, and body mass index emerged as correlates of accelerometer assessed light, moderate, and vigorous physical activity, and sedentary time among lung cancer survivors. Implications for Cancer Survivors: Identifying correlates of physical activi ty and sedentary time may aid in the development of targeted behavioral interventions for this population.